Corneal Ulcer Profile in Saiful Anwar Hospital Malang 2013-2014 - Nuke Erlina Mayasari (Majalah Oftalmologi Indonesia, 2018)
Background : The study aims to describe clinical profile of corneal ulcer patients in Saiful Anwar Hospital Malang. Method : Retrospective study was used to evaluate the medical record of corneal ulcer patients that were diagnosed by Infection and Immunology subdivision in Saiful Anwar Hospital, Malang, from January 2013 to December 2014. Data included patient’s gender, age, occupation, chief complaint, predisposing factors, visual acuity, corneal ulcer grading, microbiology examination, pharmacological therapy, surgical intervention and the clinical evaluation of treatment with slitlamp. Result : As many as 81 males and 26 females with corneal ulcer which showed the highest frequency was at the age of 41 to 50 years old (33.64%) and 69.16% cases had severe ulcers. Farmers were the most affected (46.73%). Trauma was the leading predisposing factors (78.50%) and plant material as the most cause (42.85%). Red eye was the most chief complaint in 40.19% patients. Visual acuity was 2/60-LP+ in 73.83% patients. Gram positive cocci were obtained in 72.90% patients, whereas fungi was obtained in 29.97% patients from Gram and KOH staining. Coagulase-negative staphylococcus was the most frequently detected organism in 22.43% patients amongst positive isolates. Quinolones are given in 39.25% patients, aminoglycosides in 32.71% patients, and itraconazole in 28.04% patients. As 21.50% patients needed amnion membrane transplantation. We found improvements upon the condition in 47.66% patient after the treatment evaluation. Conclusion : corneal ulcer diagnosis relies upon the complaint, predisposing factor, clinical and laboratory findings. Early and adequate treatment provides clinical improvement.